Code generation in AlphaZ - Srinivasa, Pradeep, author; Rajopadhye, Sanjay Vishnu, advisor; Böhm, Anton Pedro Willem, 1948-, committee member; Reisfeld, Bradley, committee member (Colorado State University. Libraries, 2011)
Computer architecture technology is evolving rapidly. Many of the programs written for a specific architecture are not very useful when a new architecture evolves. They have to be either modified or rewritten to suit the new architectures. Instead one can write a high level program and feed this to a tool which can produce code for different architectures. AlphaZ is such a tool which takes a high level program and helps us to analyze, transform and generate code for different architectures. In this thesis, we develop a code generation framework in AlphaZ, which takes equations as programs called alphabets program. Alphabets is a high level abstraction language which allows us to write equational programs. Equational programs consists of a set of equations along with their associated domains. We describe how code is generated in our code generation framework by taking an Alphabets program and the necessary target mapping specification. We illustrate how different code generators can be developed by extending the existing modules in our code generation framework.